2015
DOI: 10.1038/srep08282
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling reveals deep chemical divergence between two morphotypes of the zoanthid Parazoanthus axinellae

Abstract: Metabolomics has recently proven its usefulness as complementary tool to traditional morphological and genetic analyses for the classification of marine invertebrates. Among the metabolite-rich cnidarian order Zoantharia, Parazoanthus is a polyphyletic genus whose systematics and phylogeny remain controversial. Within this genus, one of the most studied species, Parazoanthus axinellae is prominent in rocky shallow waters of the Mediterranean Sea and the NE Atlantic Ocean. Although different morphotypes can eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 43 publications
5
38
0
Order By: Relevance
“…Specifically, we used three species of anthozoans (cnidarians): Parazoanthus axinellae (Schmidt, 1862) , Leptopsammia pruvoti (de Lacaze‐Duthiers, 1897), and Alcyonium acaule (Marion, 1878); six species of demosponges (poriferans): Agelas oroides (Schmidt, 1864), Axinella polypoides (Schmidt, 1862), Axinella damicornis (Esper, 2784), Crambe crambe (Schmidt, 1862), Dysidea avara (Schmidt, 1862), and Petrosia ficiformis (Poiret, 1789); and one species of ascidian (tunicate): Cystodytes dellechiajei (Della Valle, 1877) (See Supporting information Methods , Figure and Table ). For Parazoanthus axinellae , two different and easily distinguished morphotypes were used: the rather yellow and thin “slender” morphotype, which mostly lives in rocky substrates but can also usually be found as an epibiont on demosponges, and the bright orange “stocky” morphotype, which is mainly found in primary substrates (Cachet et al, ). We distinguished between these two morphotypes because of the ongoing scientific debate about whether they could, in fact, be two separated species (Cachet et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we used three species of anthozoans (cnidarians): Parazoanthus axinellae (Schmidt, 1862) , Leptopsammia pruvoti (de Lacaze‐Duthiers, 1897), and Alcyonium acaule (Marion, 1878); six species of demosponges (poriferans): Agelas oroides (Schmidt, 1864), Axinella polypoides (Schmidt, 1862), Axinella damicornis (Esper, 2784), Crambe crambe (Schmidt, 1862), Dysidea avara (Schmidt, 1862), and Petrosia ficiformis (Poiret, 1789); and one species of ascidian (tunicate): Cystodytes dellechiajei (Della Valle, 1877) (See Supporting information Methods , Figure and Table ). For Parazoanthus axinellae , two different and easily distinguished morphotypes were used: the rather yellow and thin “slender” morphotype, which mostly lives in rocky substrates but can also usually be found as an epibiont on demosponges, and the bright orange “stocky” morphotype, which is mainly found in primary substrates (Cachet et al, ). We distinguished between these two morphotypes because of the ongoing scientific debate about whether they could, in fact, be two separated species (Cachet et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was heated at reflux for 1 h. The solvent was removed, and the residue was purified by column chromatography (RP-18, H 2 NH) ppm. At 0°C, this solution was added dropwise to a mixture of l-arginine methyl ester hydrochloride (2.340 g, 8.90 mmol, 1.0 equiv.)…”
Section: -[2-hydroxy-2-(4-methoxyphenyl)ethyl]-5-methylimidazolidin-mentioning
confidence: 99%
“…[1] Figure 1 shows the optically active members of the family (parazoanthines A, D, F, G, and I). [2] This sponge has also been a source of the pyrrole-imidazole alkaloids in which we have an ongoing research interest. [1,2] The parazoanthines appear to occur exclusively in those specimens of P. axinellae that grow on other organisms such as the sponge Cymbaxinella sp.…”
Section: Introductionmentioning
confidence: 99%
“…Trade-off between the specialized metabolism, and the primary metabolism dedicated to essential biochemical processes such as growth and reproduction can be assessed by this approach (Ivanisevic et al 2011b). Bioactivities of extracts can be directly correlated to the expression level of targeted metabolites (Cachet et al 2015;Martí et al 2003;Reverter et al 2016), and metabotypes were shown to explain bioactivity patterns (Ivanisevic et al 2011b). However, metabolomics doesn't match necessarily bioactivity assessment.…”
Section: Introductionmentioning
confidence: 99%